Does Adjuvant Chemotherapy Dose Modification Have an Impact On the Outcome of Patients diagnosed with Advanced Stage Ovarian Cancer? An NRG Oncology/Gynecologic Oncology Group Study - Olawaiye, Alexander B. (Gynecol Oncol, 2018)
PURPOSE: To determine the relationship between chemotherapy dose modification (dose adjustment or treatment delay), overall survival (OS) and progression-free survival (PFS) for women with advancedstage epithelial ovarian carcinoma (EOC) and primary peritoneal carcinoma (PPC) who receive carboplatin and paclitaxel. METHODS: Women with stages III and IV EOC and PPC treated on the Gynecologic Oncology Group phase III trial, protocol 182, who completed eight cycles of carboplatin with paclitaxel were evaluated in this study. The patients were grouped per dose modification and use of granulocyte colony stimulating factor (G-CSF). The primary end point was OS; Hazard ratios (HR) for PFS and OS were calculated for patients who completed eight cycles of chemotherapy. Patients without dose modification were the referent group. All statistical analyses were performed using the R programming language and environment. RESULTS: A total of 738 patients were included in this study; 229 (31%) required dose modification, 509 did not. The well-balanced for demographic and prognostic factors. The adjusted hazard ratios (HR) for disease progression and death among dose-modified patients were: 1.43 (95% CI, 1.19–1.72, P < 0.001) and 1.26 (95% CI, 1.04–1.54, P = 0.021), respectively. Use of G-CSF was more frequent in dose-modified patients with an odds ratio (OR) of 3.63 (95% CI: 2.51–5.26, P < 0.001) compared to dose-unmodified patients. CONCLUSION: Dose-modified patients were at a higher risk of disease progression and death. The need for chemotherapy dose modification may identify patients at greater risk for adverse outcomes in advanced stage EOC and PPC.